Paradigm model of online learning experience during COVID-19 crisis in higher education - Huang, Junjun; Yoon, Dohye (Frontiers in Education, 2023)
The paper explores qualitative research on university students’ online learning experience process at the higher education level. The study uses a grounded theory for framing 25 university students with semi-structured in-depth interviews and structuring the paradigm model of university students’ online learning experience. A paradigm model illustrating this developmental process is presented, which includes the casual and contextual condition that caused and evolve the central phenomenon for their online learning, the strategies used by the students to overcome external/internal disturbance in continuing their learning process, the conditions that helped/hindered those strategies, and the consequences. Finally, the following meaning units were discovered through the preceding paradigm model. The students started learning with a negative impression of unfamiliar learning methods such as online learning, but over time, they improved their self-management ability and gained a broader understanding of self-discipline. In the midst of this, competence of digital literacy according to generational differences were also discovered as one of the factors affecting learning, forming a virtual community and increasing personal learning through online interaction. Lastly, the implications of the overall learning ecology for what role online learning will play in future forms of learning were also considered. Based on this analysis of students’ online learning experiences, the direction for online learning was suggested.